Analisa Kerugian Head Akibat Perluasan Dan Penyempitan Penampang Pada Sambungan 90o - Ahmad Yani; Ratnawati; Ardyanto Darmanto (STTI Bontang, 2021)
PVC pipe (polyvinyl chloride), galvanized, and stainless steel are types of pipes that are widely used, especially for delivering clean water to people's homes or in the industrialized world. This research was conducted by collecting data such as: flow rate (Q), pressure height (h), pipe flow velocity (v), time (s), and head loss (H), data were collected and calculated to determine pressure loss, effect variations in discharge changes and loss coefficients. From the experimental results, it was found that for the narrowing of the cross section at a discharge of 25 liters / second the value of the head loss was greater, which was located in the galvanic pipe, namely 0.09568, then followed by a discharge of 20 liters / second the value was 0.06454 and a discharge of 15 ltr / second the value was 0 , 03723. While the smallest value in panampang narrowing lies in PVC pipe, at a discharge of 25 ltr / second the value is 0.05957, at a discharge of 20 ltr / second the value is 0.03989 and at a discharge of 15 ltr / second the value is 0.02303. Likewise in the expansion of the cross-section, the greatest value lies in the galvanized pipe. For a debit of 25 ltr / second the value obtained is 0.03526, a debit of 20 ltr / second the value is 0.02355, a debit of 15 ltr / second the value is 0.01352. While the smallest value is located on the stainless steel pipe, the value is 0.02688 for the flow rate of 25 liters / second, the value for 20 liters / second is 0.01811, the value for 15 liters / second is 0.01044.